Tricky Trigonometry (Mathathon Problem 9)

Level 1

Find the value of

sec 2 ( tan 1 2 ) + cosec 2 ( cot 1 3 ) \sec^{2}(\tan^{-1} 2) + \cosec^{2}(\cot^{-1} 3)


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

By the identity sin 2 x + cos 2 x = 1 \sin^2{x}+\cos^2{x}=1

We can divide both sides by sin 2 x \sin^2 x and cos 2 x \cos^2 x to get the following identities respectively:

  • 1 + cot 2 x = cosec 2 x 1+\cot^2{x}=\cosec^2{x}

  • 1 + tan 2 x = sec 2 x 1+\tan^2{x}=\sec^2{x}


sec 2 ( tan 1 2 ) = 1 + tan 2 ( tan 1 2 ) = 1 + 4 = 5 cosec 2 ( cot 1 3 ) = 1 + cot 2 ( cot 1 3 ) = 1 + 9 = 10 sec 2 ( tan 1 2 ) + cosec 2 ( cot 1 3 ) = 15 \begin{aligned} \sec^2({\tan^{-1}2})=1+\tan^2({\tan^{-1}2})=1+4&=5\\ \cosec^2({\cot^{-1}3})=1+\cot^2({\cot^{-1}3})=1+9&=10\\ \hline \\ \sec^2({\tan^{-1}2})+\cosec^2({\cot^{-1}3})&=\boxed{15} \\ \end{aligned}

Agent T
Mar 28, 2021

Using ,

s e c 2 t a n 2 = 1 \textcolor{#20A900}{sec^{2}-tan^{2}=1}

c o s e c 2 c o t 2 = 1 \textcolor{#20A900}{cosec^{2}-cot^{2}=1}

To simplify our question as

1 + t a n 2 ( t a n 1 ( 2 ) ) + 1 + c o t 2 ( c o t 1 ( 3 ) ) \textcolor{#D61F06}{1+tan^{2}(tan^{-1}(2)) +1+cot^{2}(cot{-1}(3))}

Since,

t a n ( t a n 1 ( x ) ) = ( x ) \textcolor{#20A900}{tan(tan^{-1}(x))=(x)}

= > => t a n 2 ( t a n 1 ( 2 ) ) \textcolor{#3D99F6}{tan^{2}(tan^{-1}(2))} = 2 2 \textcolor{#3D99F6}{2^{2}}

||ly c o t 2 ( c o t 1 ( 3 ) ) \textcolor{#3D99F6}{cot^{2}(cot^{-1}(3))} = 3 2 \textcolor{#3D99F6}{3^{2}}

Plugging in the above values it becomes,

1 + 4 + 1 + 9 \textcolor{#69047E}{1+4+1+9}

Now comes the trickiest part which I m unqualified for explaining ,but it gives us the ans

15 in the end

P.s. I just discovered another way of enlarging text ,that is by adding a '-' sign in the next line.

Agent T - 2 months, 2 weeks ago
Julie Éthier
Apr 1, 2021

Kevin Long
Mar 29, 2021

First, let's break the equation into two parts, sec 2 ( tan 1 2 ) \sec^2(\tan^{-1} 2) and cosec 2 ( cot 1 3 ) \cosec^2(\cot^{-1} 3) . Making a graph so we can understand the first part better, we get
(Since the side ratio is 2:1 because of the tan 1 \tan^-1 )Because we don't know the exact length of the sides, we multiply every side by a real number x x , so we can account for triangles similar to a 1-2- 5 \sqrt 5 triangle. Since tan 1 \tan^-1 is the function for reversing tan \tan , the output of tan 1 2 \tan^{-1} 2 is the red θ \theta in the bottom left corner of the triangle. Because sec \sec is 1 cos \frac{1}{\cos} , the secant of θ \theta is the hypotenuse adjacent side \dfrac{\text{hypotenuse}}{\text{adjacent side}} , which is just 5 \sqrt 5 . Since we have to square this, the output of the first part of the expression is 5 \boxed 5 .
Doing the same with the second part of the expression, we get
In this case, the aqua a a is the output of cot 1 3 \cot^{-1} 3 . Since cosec \cosec is the opposite of sin \sin , cosec a \cosec a is equal to 10 x 1 x = 1 0 \frac{\sqrt{10}x}{1x}=\sqrt 10 . cosec 2 a = 10 \cosec^{2} a=10 , so the second part of the expression is equal to 10 \boxed {10} .
Adding the 5 5 from the first part, and the 10 10 from the second, we get 5 + 10 = 15 5+10=15 , so our final answer's 15 \boxed{15} .

goodbye cyan

Kevin Long - 1 month, 3 weeks ago
Oskar Dobroczek
Mar 28, 2021

First of all, let's call arctan ( 2 ) : = α \arctan(2):=\alpha and arccot ( 3 ) : = β \text{arccot}(3):=\beta . Next, we note that sec 2 ( α ) = 1 cos 2 ( α ) = cos 2 ( α ) + sin 2 ( α ) cos 2 ( α ) = 1 + tan 2 ( α ) \sec^2(\alpha) = \frac{1}{\cos^2(\alpha)} = \frac{ \cos^2(\alpha) + \sin^2(\alpha)}{\cos^2(\alpha)} = 1+\tan^2(\alpha) and by a similar argument csc 2 ( β ) = 1 sin 2 ( β ) = sin 2 ( β ) + cos 2 ( β ) sin 2 ( β ) = 1 + cot 2 ( β ) . \csc^2(\beta) = \frac{1}{\sin^2(\beta)} = \frac{ \sin^2(\beta) + \cos^2(\beta)}{\sin^2(\beta)} = 1+\cot^2(\beta). Now this helps a lot, since arctan ( 2 ) = α tan ( ) 2 = tan ( α ) ( ) 2 4 = tan 2 ( α ) + 1 5 = 1 + tan 2 ( α ) \begin{aligned} \arctan(2) &=\alpha &\mid \tan()\\ 2 &= \tan(\alpha) &\mid ()^2\\ 4 &= \tan^2(\alpha) &\mid +1\\ 5 &=1+ \tan^2(\alpha) \end{aligned}
and arccot ( 3 ) = β cot ( ) 3 = cot ( β ) ( ) 2 9 = cot 2 ( β ) + 1 10 = 1 + cot 2 ( β ) \begin{aligned} \text{arccot}(3)&=\beta & \mid \cot()\\ 3 &= \cot(\beta) &\mid ()^2\\ 9 &= \cot^2(\beta) &\mid +1\\ 10 &=1+ \cot^2(\beta) \end{aligned} therefore sec 2 ( α ) + csc 2 ( β ) = 1 + tan 2 ( α ) + 1 + cot 2 ( β ) = 5 + 10 = 15 . \sec^2(\alpha) + \csc^2(\beta) = 1+\tan^2(\alpha)+1+\cot^2(\beta) = 5+10 = \boxed{15}.

Devbrat Dandotiya
Mar 27, 2021

Note that for any right angled triangle, say A B C \triangle ABC with B = 90 ° \angle B=90° , we have by Pythagoras Theorem,

AC 2 = AB 2 + BC 2 \text{AC}^2= \text{AB}^2 + \text{BC}^2

And dividing the given theorem, on both sides, by hypotenuse squared, i.e AC 2 \text{AC}^2 , we get,

AB 2 AC 2 + BC 2 AC 2 = 1 \dfrac{\text{AB}^2}{\text{AC}^2} + \dfrac{\text{BC}^2}{\text{AC}^2}=1

But in the right angled triangle, we define AB 2 AC 2 \dfrac{\text{AB}^2}{\text{AC}^2} as ( sin C ) 2 (\sin C)^2 and BC 2 AC 2 \dfrac{\text{BC}^2}{\text{AC}^2} as ( cos C ) 2 (\cos C)^2 for an angle C \angle C , which gives,

sin 2 θ + cos 2 θ = 1 \sin ^2 \theta + \cos ^2 \theta =1

Which holds true for all values of θ \theta . If we divide the above found equality by sin 2 θ \sin ^2 \theta or cos 2 θ \cos ^2 \theta , each gives us the following two identities,

cot 2 θ + 1 = cosec 2 θ \cot^2 \theta +1 = \cosec^2 \theta tan 2 θ + 1 = sec 2 θ \tan^2 \theta +1 = \sec^2 \theta

Thus for the problem sec 2 ( tan 1 2 ) + cosec 2 ( cot 1 3 ) \red{\sec^2(\tan^{-1}2) + \cosec^2(\cot^{-1}3)} , tan 1 2 \tan^{-1}2 and cot 1 3 \cot^{-1}3 are the angles applying to which the formulae above, we have,

tan 2 ( tan 1 2 ) + 1 + cot 2 ( cot 1 3 ) + 1 \tan^2(\tan^{-1}2) +1 + \cot^2(\cot^{-1}3)+1

Using the fact that cif \text{cif} , short for any circular function, cif ( cif 1 a ) = a \text{cif}(\text{cif}^{-1}a)= a and that cif 2 θ = cif θ × cif θ \text{cif}^2 \theta= \text{cif} \theta × \text{cif} \theta we get,

( 3 × 3 ) + 1 + ( 2 × 2 ) + 1 (3×3)+1 +(2×2)+1

= 15 =\boxed{15}

Sundar R
Mar 27, 2021

We have to use the following identities :

1 + tan^2(x) = sec^2(x)...(1) and

1 + cot^2(x) = cosec^2(x) ...(2)

Proof of (1) :

LHS = 1 + (sin^2(x) / cos^2(x)) = (cos^2(x) + sin^2(x)) / cos^2(x) = 1 / cos^2(x) = sec^2(x)

Similarly, in the case of (2) :

LHS = 1 + (cos^2(x) / sin^2(x)) = (sin^2(x) + cos^2(x))/sin^2(x) = 1 / sin^2(x) = cosec^2(x)

Now let tan(x1) = 2 ...(3) and cot(x2) = 3 ...(4)

We need to find the value of :

sec^2(x1) + cosec^2(x2)

Using identities (1) and (2), we find

sec^2(x1) + cosec^2(x2) = 1 + tan^2(x1) + 1 + cot^2(x2) = 1 + 2^2 + 1 + 3^2 (Using (3) and (4)) = 5 + 10 = 15

Morris Pearl
Mar 27, 2021

For the left part of the expression, a point with the required tangent is at coordinates (1,2). That point is (by pythagorian theorem) at a distance 5 \sqrt{5} from the origin. The secant is therefore 5 / 1 \sqrt{5}/ 1 and the left part of the sum has a value of 5.

For the right part, a point with the required cotangent at coordinates (3,1). That point is at distance 10 \sqrt{10} from the origin, and therefore the cosecant is 10 / 1 \sqrt{10} / 1 and the right part of the sum has a value of 10.

The answer is 5 plus 10, or 15.

Siddhesh Umarjee
Mar 27, 2021

s e c 2 ( t a n 1 2 ) \color{#EC7300}{sec^2(tan^{-1}~2}) + c o s e c 2 ( c o t 1 3 ) \color{#3D99F6}{cosec^2(cot^{-1}~3)} = ? =~?

In right-angled triangle, t a n = O p p o s i t e s i d e A d j a c e n t s i d e tan = \dfrac{Opposite~side}{Adjacent~side} . Let α = t a n 1 2 \angle \alpha = tan^{-1}2 . This is represented in the following right angled triangle.

Using P y t h a g o r a s T h e o r e m Pythagoras~Theorem , hypotenuse = 5 \sqrt{5}

s e c α = H y p o t e n u s e A d j a c e n t = 5 1 sec ~ \alpha = \dfrac{Hypotenuse}{Adjacent} = \dfrac{\sqrt{5}}{1}

Therefore, s e c 2 ( t a n 1 2 ) = 5 \color{#EC7300}{sec^2 (tan^{-1}~2)} = 5


In right-angled triangle, c o t = A d j a c e n t s i d e O p p o s i t e s i d e cot = \dfrac{Adjacent~side}{Opposite~side} . Let β = c o t 1 3 \angle \beta = cot^{-1}3 . This is represented in the following right angled triangle.

Using P y t h a g o r a s T h e o r e m Pythagoras~Theorem , hypotenuse = 10 \sqrt{10}

c o s e c β = H y p o t e n u s e O p p o s i t e = 10 1 cosec ~ \beta = \dfrac{Hypotenuse}{Opposite} = \dfrac{\sqrt{10}}{1}

Therefore, c o s e c 2 ( c o t 1 3 ) = 10 \color{#3D99F6}{cosec^2 (cot^{-1}~3)} = 10


s e c 2 ( t a n 1 2 ) \color{#EC7300}{sec^2(tan^{-1}~2}) + c o s e c 2 ( c o t 1 3 ) \color{#3D99F6}{cosec^2(cot^{-1}~3)} = 5 + 10 = 15 =5+10=15

NOTE: Any triangles similar to the given triangles will also give the same result

Omek K
Mar 27, 2021

First let tan 1 ( 2 ) \tan^{-1}(2) = x , then sec²( tan 1 ( 2 ) \tan^{-1}(2) ) = sec²(x)

Since tan(x) = 2
sin ( x ) cos ( x ) \frac{\normalsize\sin(x)}{\normalsize\cos(x)} = 2 1 \frac{2}{1}
Assuming sin(x) = 2k and cos(x) = 1k

Now using sin²(x) + cos²(x) = 1, we get
1 = 4 k ² + k ² = 5 k ² k ² = 1 5 k = 1 5 0.5 \begin{aligned} 1&= 4k² + k²\\ &= 5k²\\ k²&= \frac{1}{5}\\ k&= \frac{1}{5^{0.5}} \end{aligned}

Now we get cos(x) as ± \pm 1 5 0.5 \frac{1}{5^{0.5}} .

Then,
sec ( x ) = ± 5 0.5 sec 2 ( x ) = 5. \begin{aligned} \sec(x)&= \pm5^{0.5}\\ \sec^2(x)&= 5. \end{aligned}

Therefore sec²( tan 1 ( 2 ) \tan^{-1}(2) ) = 5.
A similar procedure can be used to obtain cosec²( cot 1 ( 3 ) \cot^{-1}(3) ) = 10.
Then the answer is 5 + 10 = 15.

Zakir Husain
Mar 27, 2021

A = sec 2 ( tan 1 2 ) + cosec 2 ( cot 1 3 ) A=\blue{\sec^2(\tan^{-1}2)}+\red{\cosec^2(\cot^{-1}3)} l e t x = tan 1 2 tan x = 2 let\space x=\blue{\tan^{-1}2}\Rightarrow \blue{\tan x=2} 4 = tan 2 x = sec 2 x 1 5 = sec 2 x \Rightarrow 4=\tan^2 x = \sec^2 x - 1\Rightarrow 5= \sec^2 x sec 2 ( tan 1 2 ) = 5 \Rightarrow \blue{\sec^2(\tan^{-1}2) = 5} l e t y = cot 1 3 cot y = 3 let\space y=\red{\cot^{-1}3}\Rightarrow \red{\cot y=3} 9 = cot 2 y = cosec 2 y 1 10 = cosec 2 y \Rightarrow 9=\cot^2 y = \cosec^2 y - 1\Rightarrow 10= \cosec^2 y cosec 2 ( cot 1 3 ) = 10 \Rightarrow \red{\cosec^2(\cot^{-1}3) = 10} A = 5 + 10 = 1 5 \Rightarrow A=\blue{5}+\red{10}=\boxed{\red{1}\blue{5}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...